1995
DOI: 10.1128/iai.63.4.1158-1164.1995
|View full text |Cite
|
Sign up to set email alerts
|

Anti-gamma interferon and anti-interleukin-6 antibodies affect staphylococcal enterotoxin B-induced weight loss, hypoglycemia, and cytokine release in D-galactosamine-sensitized and unsensitized mice

Abstract: Administration of staphylococcal enterotoxin B (SEB) to BALB/c mice was found to induce a cytokine release syndrome hallmarked by weight loss and hypoglycemia. A neutralizing monoclonal antibody against gamma interferon (IFN-␥) given before SEB counteracted weight loss and prevented hypoglycemia. This protective effect of anti-IFN-␥ antibody was associated with decreased IFN-␥ levels in serum; tumor necrosis factor (TNF) and interleukin-6 (IL-6) levels remained unchanged. A monoclonal anti-IL-6 antibody, known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 24 publications
2
41
0
2
Order By: Relevance
“…Furthermore, elevated IL-6 infusion and exercise has been seen to attenuate endotoxin-induced increases in TNF-α in humans [74]. The fact that TNF-α levels are markedly elevated in anti-IL-6-treated mice [100,101] adds further support that circulating IL-6 is involved in the regulation of TNF-α. Another anti-inflammatory IL-6 function is the stimulation of IL-1ra and IL-10 [86] antiinflammatory cytokines, in addition to the release of soluble TNF-α receptors, sTNF-r1 and sTNF-r2 [77].…”
Section: Exercise and Inflammationmentioning
confidence: 93%
“…Furthermore, elevated IL-6 infusion and exercise has been seen to attenuate endotoxin-induced increases in TNF-α in humans [74]. The fact that TNF-α levels are markedly elevated in anti-IL-6-treated mice [100,101] adds further support that circulating IL-6 is involved in the regulation of TNF-α. Another anti-inflammatory IL-6 function is the stimulation of IL-1ra and IL-10 [86] antiinflammatory cytokines, in addition to the release of soluble TNF-α receptors, sTNF-r1 and sTNF-r2 [77].…”
Section: Exercise and Inflammationmentioning
confidence: 93%
“…The suppressive effect occurs at the level of transcription in human peripheral blood mononuclear cells (Schindler et al, 1990). Following endotoxin infusion in vivo, levels of TNF were markedly elevated in anti-IL-6-treated mice (Matthys, Mitera, Heremans, Van Damme, Billiau, 1995) and an IL-6 deficient knock-out mice compared with control mice, suggesting that circulating IL-6 regulates TNF levels (Mizuhara, 1994).…”
Section: Pro-and Anti-in¯ammatory Cytokinesmentioning
confidence: 99%
“…TNF-α and interleukin (IL)-6 are tightly linked, thus TNF-α stimulates IL-6 production. However, in vitro studies (10) as well as animal studies (11,12) suggest that IL-6 may inhibit TNF-α production, and it has been suggested that IL-6 should be classified as an antiinflammatory cytokine (13) Exercise induces increased plasma catecholamine levels (6), and it has recently been demonstrated that epinephrine infusion inhibited endotoxin-induced in vivo TNF-α appearance and also increased IL-10 release (14). Therefore, we hypothesized that exercise would inhibit an endotoxin-stimulated increase in circulating levels of TNF-α.…”
mentioning
confidence: 99%